Assessment on Flood Hazard of Different Return Periods in Mueang Phrae District, Phrae Province, Thailand - Promping, Thanasit; Tingsanchali, Tawatchai; Nimpia, Thanawat (การประชุมวิศวกรรมโยธาแห่งชาติ ครั้งที่ 30, 2025)
Floodings occur frequently in Phrae Province, Thailand, particularly in Mueang Phrae District, which locates within the upper Yom River Basin. The Yom River is a major tributary of the Yom River Basin which significantly influences flood runoff of the River Basin. The recent floods in 2024 caused substantial damages to infrastructure, agriculture, and communities, underscoring the need for effective flood management. This study assesses flood hazards in Mueang Phrae District by evaluating flood-affected areas at different return periods of 2, 5, 10, 25, 50, 100, and 500 years. Hydrodynamic modeling was conducted using the well-known HEC-RAS model developed by the U.S. Army Corps of Engineers, along with topographic data, river cross-sections, and historical daily water level data. Both model calibration and validation demonstrated high model performance, with Coefficient of Determination (R²) values of 0.95 and 0.87, Nash-Sutcliffe Efficiency (NSE) of 0.95 and 0.87, Percent Bias (PBIAS) of 1.10% and -1.60%, Mean Absolute Error (MAE) of 0.01 and 0.33, and Root Mean Square Errors (RMSE) of 0.28 and 0.38 for the flood periods during 2000-2011 and 2012-2023. Flood hazard maps were created to identify flood-prone areas for each return period, covering the following extents: 4.23, 5.86, 7.35, 8.06, 9.48, 10.51, and 11.80 km² for the 2, 5, 10, 25, 50, 100, and 500 years, respectively. These areas were classified into five hazard levels: very low, low, medium, high, and very high according to the flood damages. The findings contribute to a better understanding of flood hazards in Mueang Phrae District and provide valuable insights for flood disaster adaptation measures, preparedness, and enhancing community resilience to future floods.